52nd IEEE Conference on Decision and Control 2013
DOI: 10.1109/cdc.2013.6760712
|View full text |Cite
|
Sign up to set email alerts
|

A spectral operator-theoretic framework for global stability

Abstract: Abstract-The global description of a nonlinear system through the linear Koopman operator leads to an efficient approach to global stability analysis. In the context of stability analysis, not much attention has been paid to the use of spectral properties of the operator. This paper provides new results on the relationship between the global stability properties of the system and the spectral properties of the Koopman operator. In particular, the results show that specific eigenfunctions capture the system sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 13 publications
0
59
0
Order By: Relevance
“…Thus, the Lyapunov function decays everywhere under action of the adjoint Liouville operator and is related to its properties and those of the Koopman operator family. In [113], it has been shown that global stability of a fixed point can be established through the existence of a set of C 1 eigenfunctions of the Koopman operator associated with the eigenvalues of the Jacobian of the vector field, and that Koopman eigenfunctions can be used to define a Lyapunov function and contracting metrics. A numerical scheme based on a Taylor expansion is proposed to compute stability properties including the domain of attraction [113].…”
Section: U Q F Z 1 5 K E Z W O W V F S U Z a W Q C I 4 D Q O O Q C mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Lyapunov function decays everywhere under action of the adjoint Liouville operator and is related to its properties and those of the Koopman operator family. In [113], it has been shown that global stability of a fixed point can be established through the existence of a set of C 1 eigenfunctions of the Koopman operator associated with the eigenvalues of the Jacobian of the vector field, and that Koopman eigenfunctions can be used to define a Lyapunov function and contracting metrics. A numerical scheme based on a Taylor expansion is proposed to compute stability properties including the domain of attraction [113].…”
Section: U Q F Z 1 5 K E Z W O W V F S U Z a W Q C I 4 D Q O O Q C mentioning
confidence: 99%
“…In [113], it has been shown that global stability of a fixed point can be established through the existence of a set of C 1 eigenfunctions of the Koopman operator associated with the eigenvalues of the Jacobian of the vector field, and that Koopman eigenfunctions can be used to define a Lyapunov function and contracting metrics. A numerical scheme based on a Taylor expansion is proposed to compute stability properties including the domain of attraction [113]. These ideas have been further extended to examine global stability properties of hyperbolic fixed points and limit cycles and also for non-analytical eigenfunctions [112].…”
Section: U Q F Z 1 5 K E Z W O W V F S U Z a W Q C I 4 D Q O O Q C mentioning
confidence: 99%
“…Also, using approximative linear operators enables the application of linear systems algorithms and theory to nonlinear systems. Applying linear stability analysis to establish global stability is one example (Mauroy and Mezic, 2013). Sootla et al (2016) leverage the Koopman operator in the design of temporal pulse control of bistable monotone systems.…”
Section: Literature Review On the System Identification And Finite LImentioning
confidence: 99%
“…We will call the family of operators U t indexed by time t the Koopman operator of the continuous-time system (1). This family was defined for the first time in [3], for Hamiltonian systems.…”
Section: Introductionmentioning
confidence: 99%